Sluggish cognitive tempo: An examination of clinical correlates for adults with autism. (August 2020) - Brewe, Alexis M; Simmons, Grace Lee; Capriola-Hall, Nicole N; White, Susan W
Adults with autism spectrum disorder often experience co-occurring mental health problems such as attention-deficit/hyperactivity-disorder, as well as impairments in executive function. Sluggish cognitive tempo, a cluster of behaviors including slow processing, daydreaming, and mental fogginess, has been shown to be associated with attention-deficit/hyperactivity-disorder. This study was designed to assess sluggish cognitive tempo in young adults with autism spectrum disorder. Specifically, we sought to establish a preliminary estimate of clinically significant sluggish cognitive tempo symptoms and to better understand its phenomenology and associations with executive function and psychiatric symptoms in the context of autism spectrum disorder. Young adults with autism spectrum disorder ( n = 57; age 16–25 years; 84.2% male) completed a laboratory-based executive function task, and parents and participants completed measures of the participants' sluggish cognitive tempo, attention-deficit/hyperactivity-disorder, depression, and anxiety symptoms. Nearly one-third of the sample exhibited clinically impairing levels of sluggish cognitive tempo. Although sluggish cognitive tempo and attention-deficit/hyperactivity-disorder symptoms were significantly correlated, findings suggest the constructs are distinct. Results also suggest that increased sluggish cognitive tempo is related to executive function impairment and depression, but not anxiety symptoms. Considerations for assessment and long-term impacts of sluggish cognitive tempo for adults with autism spectrum disorder are discussed. Lay abstract: Adults with autism spectrum disorder often experience a range of co-occurring mental health problems such as attention-deficit/hyperactivity-disorder, as well as difficulties with executive function. Sluggish cognitive tempo, a cluster of behaviors including slow processing, daydreaming, and mental fogginess, has been shown to be associated with attention-deficit/hyperactivity-disorder, and limited research has suggested that individuals with autism spectrum disorder may experience sluggish cognitive tempo. We examined co-occurring mental health problems and executive function in 57 young adults with autism spectrum disorder, aged 16–25 years to better understand sluggish cognitive tempo in autism spectrum disorder. Parents of the young adults answered questions about their children's sluggish cognitive tempo, attention-deficit/hyperactivity-disorder, depression, and anxiety symptoms, and the young adults completed tests of their executive function. Results demonstrated that nearly one-third of the sample exhibited clinically impairing levels of sluggish cognitive tempo. Although sluggish cognitive tempo and attention-deficit/hyperactivity-disorder symptoms were related, our findings suggest they are not the same constructs. Increased sluggish cognitive tempo is related to more difficulties with executive function and increased depression, but not anxiety symptoms. Results demonstrate that sluggish cognitive tempo may pose heightened difficulties for adults with autism spectrum disorder, making it an important construct to continue studying. Considerations for assessment and long-term impacts of sluggish cognitive tempo for adults with autism spectrum disorder are discussed.